Independent Work Management Through Adaptive Teaching-Learning Environment APA-Prolog - Ríos-Rodríguez, Lydia Rosa (2021)
Reaching independence in learning is essential in professional formation. In this line, this article aims to describe the use of the APA-Prolog environment in the teaching‑learning process adjusted to the dynamics of the independent work management process. The study was conducted with a quantitative methodological approach and a non-experimental descriptive design. A survey with a Likert scale type was conducted to 22 students from the Computing Engineering program at the University of Sancti Spiritus to measure the use of the environment adjusted to the planning, orientation, execution, and control-evaluation phases. The data were analyzed through the calculus of the mean values of answers, the percentage of representativeness, and the typical deviation. The results showed the ordered fulfillment of the phases that allowed the recognition of the cognitive independence abilities and the interaction with simulators, trainers, tutorials, evaluators, and hypermedia conceptual maps, which were controlled by intelligent agents that made decisions based on the previous students’ knowledge. It was concluded that the development of cognitive independence abilities—such as reading, analysis, interpretation, deduction, and processing—was stimulated. It was also concluded that the students manage the knowledge by means of free or assisted browsing according to their choice and the type of activity to solve and that the teaching-learning adaptive environments favor a dynamic educative process based on the student.